PERAN SERVANT LEADERSHIP DAN PERSON ORGANIZATION FIT DALAM MENURUNKAN TURNOVER INTENTION MELALUI ORGANIZATIONAL COMMITMENT - Titiep Pramuda Wardani; Rifdah Abadiyah (International Journal on Orange Technologies, 2021)
Human resources are valuable assets in an organization which can bring significant effect in achieving its objectives organization and is in the determination of the capital stock of the company. The influence of servant leadership and person organization fit against turnover intention with organizational commitment as variable no intervening. The research used a quantitative study. The research was taken at PT. XYZ. The research population was a production line whole workers in PT. XYZ 336 employees. The research sample was 128 people with purposive sampling. The data collection used questioners. The data analysis used path analysis with SPSS data software. The research results show that servant leadership and person organization fit had an influence on comittment organizational and turnover intention then servant leadership and person organization fit had an influence on turnover intention through comittment organizational as no intervening variable production line PT. XYZ.